113k views
4 votes
Algebra 2 question..

User CodingRat
by
4.8k points

1 Answer

2 votes

We are supposed to solve the equation


6(2x-1)-12=3(7x+4)

Here, we need to apply the distributive laws on both sides.

Comment: The distributive laws say that


a(b+c)=ab+ac\text{ and }(b+c)a=ba+ca

Using this comment we get


6(2x-1)=6(2x)+6(-1)=12x-6
3(7x+4)=3(7x)+3(4)=21x+12

Then, our equation becomes


(12x-6)-12=21x+12
12x-18=21x+12

Now, let's apply the rule: terms with x on the right-hand side, and the rest on the left-hand side, to obtain


-18-12=21x-12x
-30=9x
x=(-30)/(9)=-(10)/(3)

User Miyuru
by
5.1k points